Effect of Thermophilic Nitrate Reduction on Sulfide Production in High Temperature Oil Reservoir Samples - Okpala, Gloria N.; Chen, Chuan; Fida, Tekle; Voordouw, Gerrit (Frontiers in Microbiology, 2017)
Oil fields can experience souring, the reduction of sulfate to sulfide by sulfate-reducing microorganisms. At the Terra Nova oil field near Canada’s east coast, with a reservoir temperature of 95oC, souring was indicated by increased hydrogen sulfide in produced waters. Microbial community analysis by 16S rRNA gene sequencing showed the hyperthermophilic sulfate-reducing archaeon Archaeoglobus in Terra Nova produced waters. Growth enrichments in sulfate-containing media at 55-70oC with lactate or volatile fatty acids yielded the thermophilic sulfate-reducing bacterium (SRB) Desulfotomaculum. Enrichments at 30-45oC in nitrate-containing media indicated the presence of mesophilic nitrate-reducing bacteria (NRB), which reduce nitrate without accumulation of nitrite, likely to N2. Thermophilic NRB of the genera Marinobacter and Geobacillus were detected and isolated at 30-50oC and 40-65oC, respectively, and only reduced nitrate to nitrite. Added nitrite strongly inhibited the isolated thermophilic SRB and thermophilic NRB and SRB could not be maintained in co-culture. Inhibition of thermophilic SRB by nitrate in batch and continuous cultures required inoculation with thermophilic NRB. The results suggest that nitrate injected into Terra Nova is reduced to N2 at temperatures up to 45oC but to nitrite only in zones from 45 to 65oC. Since the hotter zones of the reservoir (65-80oC) are inhabited by thermophilic and hyperthermophilic sulfate reducers, souring at these temperatures might be prevented by nitrite production if nitrate-reducing zones of the system could be maintained at 45-65oC.